2023
DOI: 10.3389/fvets.2023.1157935
|View full text |Cite
|
Sign up to set email alerts
|

Use of fermented Chinese medicine residues as a feed additive and effects on growth performance, meat quality, and intestinal health of broilers

Abstract: IntroductionThe purpose of this research was to investigate how dietary supplementation with fermented herbal residues (FCMR) affected birds' development capacity, quality of meat, gut barrier, and cecum microbiota.Methods540 cyan-shank partridge birds aged 47 days were chosen and divided into two groups of six replicates each and 45 birds for each replicate. The control group (CON) received a basal diet, while the trial group decreased a basic diet containing 5% FCMR.Results and discussionThe findings reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…In another study, supplementing with 3 g/kg of Lichen Bacillus fermented product enhanced the body weight and average weight of birds compared to the control group ( 23 ). Our previous research also found that supplementing with 5% fermented medicinal herb residues enhanced the FW and ADG of broilers, while decreased their feed to meat ratio ( 24 ). Consistent with previous researchers, supplementing with a certain amount of FCSF significantly improved the FW and ADG of broilers, while significantly reduced their F/G, ADFI, and mortality.…”
Section: Discussionmentioning
confidence: 83%
“…In another study, supplementing with 3 g/kg of Lichen Bacillus fermented product enhanced the body weight and average weight of birds compared to the control group ( 23 ). Our previous research also found that supplementing with 5% fermented medicinal herb residues enhanced the FW and ADG of broilers, while decreased their feed to meat ratio ( 24 ). Consistent with previous researchers, supplementing with a certain amount of FCSF significantly improved the FW and ADG of broilers, while significantly reduced their F/G, ADFI, and mortality.…”
Section: Discussionmentioning
confidence: 83%
“…Intestinal villus height (VH), crypt depth (CD) and VH/CD ratio are important indicators of intestinal structural integrity ( 49 ). Longer intestinal villus height and shallower crypt depth indicate better healthy digestion and absorption of microorganisms ( 10 ), improved intestinal mucosal differentiation, and enhanced capacity for digestion and absorption ( 50 ). Previous studies have found that adding probiotics, forsythia extract, natural pepper extract, and ellagic acid is an alternative to antibiotics in increasing the intestinal villus height of broilers ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…This increased relative abundance of Bacteroidota contributes to the maintenance of intestinal health and the alleviation of intestinal inflammation and LPS-induced systemic inflammation [45,46]. Previous studies have suggested that the supplementation of broiler chickens with fermented herbal residues (FCMRs) increases the relative abundance of cecal Spirochaetota, which facilitates the conversion of carbohydrates to volatile fatty acids (VFAs) to provide energy to the body [47,48]. In conclusion, the addition of CME and CPN prevented the decrease in the relative abundance of beneficial bacteria caused by LPS induction and increased the number of acid-producing bacteria.…”
Section: Discussionmentioning
confidence: 99%